Optimizing Regional Asset Management During The COVID-19 Pandemic In Banten Province - Rina Dewiyanti; Didin Muhafidin; Rahman Mulyawan; Elisa Susanti (Universitas Padjadjaran, 2022)
The asset management cycle is an important component and foundation for Regional Governments in managing their assets, but in reality, the management of regional assets is still a classic problem in the Regional Government environment. One of the mandates of the Banten Province's vision contained in the Regional Medium Term Development Plan or RPJMD is to realize good governance. In connection with this, it is a manifestation of the implementation of the principles of good governance, realizing an optimal and adequate regional wealth management system is one of the demands that are expected to be realized by the community. Government Regulation Number 28 of 2020 Amendment to Government Regulation Number 27 of 2014 concerning Management of State or Regional Property is a new policy issued by the Government of Indonesia during the COVID-19 pandemic regarding the management of the regional property. This study uses a descriptive qualitative approach, and in collecting data, this study uses literature studies and internet searching. This study will discuss in more depth how to optimize regional asset management during the COVID-19 pandemic carried out by the Banten Provincial Government.